CONDITIONS FOR VALIDITY OF DEPRIVATION FROM THE COMPULSORY PORTION AND CONSEQUENCES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
Deprivation of the compulsory portion in favor of the descendants in order to be valid,it is necessary to accomplish certain conditions. Such a valid deprivation from their sidemore to cause certain consequences. Thus, in the paper we study the conditions for the validdeprivation of the compulsory portion and the caused consequences. This of course from theirside leads to the elaboration of certain theoretical dilemmas. In this regard it is especiallyimportant question whether the deprivation of the descendant in the will should state in whosefavor the deprivation is, that is, that deprivation is in favor of the descendants. Also eam ofattention is the question when there is a deprivation of the compulsory share in favor of thedescendants, whether the deprived descendant is considered to have died before the testator ornot? This is certainly important for which persons are called to inherit, ie which descendantswill inherit that part of the inheritance. Namely, the aim of the paper is to study the conditionsfor deprivation, the consequences of such deprivation, theoretical dilemmas, with appropriateapplication of comparative solutions.